Breaking chains of tobacco: empowering African American churches in West Virginia for a healthier future - Reed, Donald; Dangerfield, Truman; Robinson, Rhonda; Ray, Kenneth; Danberry, Kathy; Tieman, Kim (Frontiers in Public Health, 2024)
Across West Virginia, tobacco use continues to be a significant public health challenge. Specifically, tobacco use is linked to high poverty across the state and disproportionately affects African Americans. A faith-based tobacco prevention network was formed to address these concerns and increase education and cessation. The West Virginia African American Tobacco Prevention Network (WVAATPN) was formed in 2021 and since then has expanded its reach across the state, involving 22 congregations. The Network’s model includes annual training for lay leaders on various tobacco-related topics, tailored educational curriculum for congregations, and collaboration with national experts to enhance program efficacy. The Network has run educational and cessation workshops and promoted events such as No Menthol Sunday. Workshops have yielded positive outcomes among participants, including increased awareness of tobacco marketing tactics, higher cessation rates, and improved understanding of the health impacts of tobacco. The WVAATPN continues to expand its reach and effectiveness by advocating for policy change, enhancing community engagement, and fostering partnerships to combat tobacco-related disparities in West Virginia’s African American communities.